Microfluidic channel-based wireless charging and communication platform for microsensors with miniaturized onboard antenna. (29th September 2016) - Duan, G; Zhao, X; Seren, H R; Chen, C; Li, A; Zhang, X
Abstract: A double layer spiral antenna with side length of 380 μ m was fabricated by a multi-step electroplating process, and integrated with a commercialized passive RFID chip to realize the RF power harvesting and communication functions of a microsensor. To power up and communicate with the microchips, a single layer spiral reader antenna was fabricated on top of a glass substrate with side length of 1 mm. The microchips and the reader antenna were both optimized at the frequency of 915 MHz. Due to the small size of the reader antenna, the strength of the magnetic field decreased dramatically along the axial direction of the reader antenna, which limited the working distance to within 1 mm. To enclose the microchips within the reading range, a three-layer microfluidic channel was designed and fabricated. The channel and cover layers were fabricated by laser cutting of acrylic sheets, and bonded with the glass substrate to form the channel. To operate multiple microchips simultaneously, separation and focusing function units were also designed. Low loss pump oil was used to transport the microchips flowing inside the channel. Within the reading area, the microchips were powered up, and their ID information was retrieved and displayed on the computer interface successfully.